Birth timing after the long feeding migration in northern elephant seals. Issue 3 (17th December 2021) - Condit, Richard; Beltran, Roxanne S.; Robinson, Patrick W.; Crocker, Daniel E.; Costa, Daniel P.
Abstract: Northern elephant seals migrate long distances from feeding grounds to raise pups during a brief period on breeding beaches. Because gestation sets a parturition date months in advance, timing of the arrival must be precise; an early arrival would waste foraging time, but a late arrival would cause parturition failure. We used satellite‐tracked animals to examine this timing, establishing arrival and birth dates in 106 migrating females and estimating how far they traveled in the days just before birth. Females arrived a mean of 5.5 days prior to birth (range 1–11, SD = 1.5), and females arriving later in the breeding season had 1.8‐day shorter prebirth intervals relative to early arrivers. There was no correlation between female body condition, nor female age, and the prebirth interval. The last 15 days prior to birth, animals traveled as far as 1, 465 km. Those farthest from the colony traveled >100 km per day, three times faster than animals near the colony at the same time. Despite migrations covering several thousand kilometers while pregnant, female elephant seals were able to time their arrival within days. This allows them to maintain a precise annual birth cycle for many years consecutively.